Essays in financial economics - Biswas, Rita; Michaelides, Michael (Emerald Publishing Limited, 2019)
This volume, dedicated to John W. Kensinger, explores a variety of topics in financial economics, including firm growth, investment risks, and the profitability of the banking industry. With its global perspective, Essays in Financial Economics is a valuable addition to the bookshelf of any researcher in finance. Starting with a study examining the NYMEX Crude oil market, the first paper uses a no-arbitrage futures equilibrium cost-of-carry model that incorporates both the quality delivery option as well as the timing delivery option in the NYMEX contract. This is followed by two papers focusing on the growth of firms, one looking at a sample of S&P 500 firms in the US and one utilising a sample of firms from India's manufacturing sector. The fourth paper compares the Fama-French (FF) five-factor model for firms on the Paris Bourse with the four-factor model, exploring how the fifth factor, investment risk premium, benefits the French stock market in comparison with the profitability factor (the fourth factor). The fifth paper examines the volatility of the Indian stock market, while the sixth looks at the Italian banking industry. Closing the volume is a paper that looks at the relationship between the US Dollar Index and several emerging stock market indices using Granger Causality tests.
Keywords: Capital market.; Finance.; Business & Economics -- Finance -- General.; elektronické knihy; electronic books